The respiratory metabolism of the castes of two leaf cutting ants, Atta laevigata (F. Smith, 1858) and Atta sexdens rubropilosa forel, 1908 - Joséa, Maria [UNESP]; Beraldo, Hebling [UNESP]; Mendes, Erasmo G [UNESP] (Elsevier B.V., 1981)
1. 1. The respiration of the different castes of two species of leaf-cutting ants, Atta laevigata and Atta sexdens rubropilosa was measured in both workers and sexed forms. 2. 2. The respiratory rates (μl O2/mg(live)/hr) were, in A. laevigata, 0.644 (gardeners), 0.594 (cutters), 0.354 (soldiers), 0.233 (males) and 0.085 (females); in A. s. rubropilosa, 0.803 (gardeners), 0.748 (cutters), 0.510 (soldiers), 0.375 (males) and 0.274 (females), significantly higher than A. laevigata. 3. 3. All castes considered, the b-values of the equation relating oxygen consumption and weight in A. laevigata (0.53) were significantly different from that in A. s. rubropilosa (0.73). © 1981.